The Septuagint of Jeremiah and Its Bearing on the New Covenant Passage (Jeremiah 31:31-34) - Boyd, Connor (Biblical research, 2023)
This article seeks to account for the perceived discrepancy between the Septuagint reading ἠμέλησα αὐτῶν ("I neglected them") and the Masoretic Text reading בָּעַ֥לְתִּי בָ֖ם "I was their husband" [NRSV]) inJer 31:32 (38:32 LXX). While the majority of scholars holds that this LXX reading reflects a variant in its Hebrew Vorlage, I will argue instead that ἠμέλησα αὐτῶν is an entirely appropriate (and indeed the earliest attested) translation of בָּעַ֥לְתִּי בָ֖ם as evidenced by (1) the lexical arguments ofWilhelm Gesenius and Joseph Kirnchi, two influential Hebrew grammarians and exegetes; (2) the Syriac translation of Jer 31:32; (3) the immediate context of Jer 31:31-34; and (4) the parallel occurrence of בָּעַ֣לְתִּי בָכֶ֑ם inJer 3:14. Understanding ἠμέλησα αὐτῶν as a valid translation of בָּעַ֥לְתִּי בָ֖ם not only resolves this perceived discrepancy between the LXX and MT in Jer 31:32 but also calls for a reinterpretation of the new covenant passage as it stands in the MT.